Leadership and employee motivation : exploring the role of virtual communication - Bruns, Paula Antonia (2024)
This study explores the relationship between virtual communication, leadership, and employee motivation, emphasizing the roles of autonomy, competence, and relatedness as outlined in the Self-Determination Theory (SDT) and six key leadership functions essential for team success, based on the Functional Leadership Approach (FLA). Data were gathered through an online survey of 190 participants. While significant correlations were found between motivation and leadership effectiveness, the assumption that virtual communication directly impacts employee motivation and perceived leadership effectiveness was not supported. Specifically, supporting a positive social climate emerged as a crucial function for addressing all needs. For the need for competence, the leadership function of "establishing expectations and goals" was identified as particularly significant. Notably, gender differences emerged, with male participants reporting lower satisfaction in specific leadership functions, suggesting possible gender-based preferences in virtual work environments. The study reveals that while virtual communication has a limited direct effect on employee motivation and leadership effectiveness, it highlights the crucial link between leadership and motivation. The strong correlation between effective leadership and the fulfillment of employees' psychological needs underscores the vital role leadership plays in driving motivation. Although virtual communication alone did not show a significant direct impact, there is a possibility that certain leadership behaviors may promote greater motivation in virtual environments. Importantly, future research should explore the mechanisms through which virtual communication can positively impact motivation and leadership effectiveness, as this remains a key area for understanding how virtual environments can enhance employee engagement and performance across different cultural and organizational contexts.